2017
DOI: 10.13057/nusbiosci/n090214
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacillus subtilis and B. licheniformis potentials as probiotic bacteria in Vanamei shrimp feed (Litopenaeus vannamei Boone, 1931)

Abstract: Abstract. Andriani Y, Safitri R, Rochima E, Fakhrudin SD. 2017. Characterization of Bacillus subtilis and B. licheniformis potentials as probiotic bacteria in Vanamei shrimp feed (Litopenaeus Vannamei Boone, 1931). Nusantara . This study aimed to characterize the Bacillus subtilis and Bacillus licheniformis potentials as probiotic bacteria in Vanamei shrimp feed (Litopenaeus vannamei Boone, 1931). A two-phase experimental descriptive method in a laboratory scale was applied in this study. The first phase was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Reports indicate that both the vegetative cells and spores of B. subtilis possess high bile tolerance (Sansawat & Thirabunyanon 2009; Andriani et al . 2017; Jeon et al . 2017; Liu et al .…”
Section: Bacillus Subtilis and Its Probiotic Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports indicate that both the vegetative cells and spores of B. subtilis possess high bile tolerance (Sansawat & Thirabunyanon 2009; Andriani et al . 2017; Jeon et al . 2017; Liu et al .…”
Section: Bacillus Subtilis and Its Probiotic Attributesmentioning
confidence: 99%
“…In addition to acid resistance, bile salt tolerance is also very crucial for a probiotic bacterium to sustain and overcome the horse acidic gastric environment and the presence of bile salts (Widanarni & Wahjuningrum 2012). Reports indicate that both the vegetative cells and spores of B. subtilis possess high bile tolerance (Sansawat & Thirabunyanon 2009;Andriani et al 2017;Jeon et al 2017;Liu et al 2017;Szmigiel et al 2019).…”
Section: Ability To Adhere Survive and Multiply In The Gastrointestimentioning
confidence: 99%
“…In studies conducted by [77] it was revealed that Bacillus subtilis were intolerant to acidic condition. During co-culture of Lactobacillus (five strains) or Lactococcus (two strains) with Bacillus cereus, organic acids and other potentially antimicrobial metabolites are produced.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to survive in the gastrointestinal tract environment is an important requirement for the application of probiotics as additives in livestock animal feeds ( 38 , 39 ). The pH range of animal stomach is around pH 2.0 to 3.0 which rarely raises above pH 3.0 even when satiated ( 40 ) and the bile salt concentration in the digestive tract is around 0.3% to 0.5% ( 41 ). In this study, B4 showed the ability to survive at pH 3.0 for 5 h, which is similar to Bacillus licheniformis CK1 strain isolated by Tsui Chun Hsu ( 42 ).…”
Section: Discussionmentioning
confidence: 99%